Phase Transitions in Two-Dimensional Complex Plasmas - Knapek, Christina A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two experimental studies reported in this thesis contribute important new knowledge about phase transitions in two-dimensional complex plasmas: in one case a determination of the coupling parameter (ratio of mean potential to mean kinetic energy of the particles in an ensemble), and in the other a detailed characterization of the non-equilibrium recrystallization of a two-dimensional system. The latter results are used to establish the connection between structural order parameters and the kinetic energy, which in turn gives novel insights into the underlying physical processes determining the two-dimensional phase transition.
Introduction -- Complex Plasmas -- Experiments -- Data Analysis Techniques -- Estimation of the Coupling Strength -- Theory of Phase Transitions in 2D Systems -- Recrystallization of a 2D Plasma Crystal -- Summary and Outlook -- Estimation of Uncertainties in the Particle Coordinates -- Bond of Orientational Order -- Curriculum Vitae.
Keywords: Physics; Physics; Phase Transitions and Multiphase Systems; Plasma Physics; Surface and Interface Science, Thin Films